2013
DOI: 10.3109/08880018.2013.834400
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric Burkitt's Lymphoma and Diffuse B-Cell Lymphoma: Are Surveillance Scans Required?

Abstract: Outcomes in pediatric B-Non-Hodgkin Lymphoma have improved with intensive chemotherapy protocols, with long-term survival now over 80%. However, long-term adverse effects of therapy and poor outcomes for patients who relapse remain challenges. In this study, we aimed to evaluate the potential risks and benefits of routine relapse surveillance imaging after the completion of therapy. We reviewed 44 B NHL patients diagnosed and treated at Texas Children’s Cancer Center in the period between 2000 to 2011. All cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In adults, imaging surveillance with CT is performed, as described previously. In children, routine surveillance with cross-sectional imaging may not be warranted for patient achieving complete response after therapy given overall low rates of relapse along with increased costs and added risks of radiation exposure [51]. Thus, surveillance may be performed with cervical and abdominal ultrasound with chest radiography with CT or PET/CT reserved if there are signs of relapse.…”
Section: Treatmentmentioning
confidence: 99%
“…In adults, imaging surveillance with CT is performed, as described previously. In children, routine surveillance with cross-sectional imaging may not be warranted for patient achieving complete response after therapy given overall low rates of relapse along with increased costs and added risks of radiation exposure [51]. Thus, surveillance may be performed with cervical and abdominal ultrasound with chest radiography with CT or PET/CT reserved if there are signs of relapse.…”
Section: Treatmentmentioning
confidence: 99%
“…There are also data demonstrating that PET scanning can produce false-negative results; therefore, a biopsy to prove residual or recurrent disease is required. 24 …”
Section: Non-hodgkin Lymphomamentioning
confidence: 99%
“…Hence, a current recommendation is to tailor surveillance imaging to patients with high risk of recurrence and high likelihood of benefit . For non‐Hodgkin lymphoma, one study showed that while three of 44 patients developed recurrence, none was diagnosed by CT or PET scans . Two studies focusing on children with sarcoma and rhabdomyosarcoma, respectively, showed that regular imaging studies neither facilitated earlier detection of recurrence nor improved overall survival .…”
Section: Discussionmentioning
confidence: 99%